Information Technology Utilization Of Young Educated Farmers In Agricultural Entrepreneurship - Siti Nurlaela; Alia Bihrajihant Raya; Sunarru Samsi Hariadi (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2022)
Information technology can help farmers develop their farming, but its utilization is still very low for farmers. This study aims to reveal the personal characteristics of educated young farmers, their entrepreneurial characteristics, their behaviour in using information technology, and their obstacles in utilizing it. This research is a descriptive exploratory with a quantitative approach. The data collection technique used a questionnaire on 124 Yogyakarta-Magelang Agricultural Development Polytechnic students in March-June 2019. Respondents were collected using the census method. The results revealed that educated young farmers prefer entrepreneurial cultivation.Meanwhile, the behaviour of utilizing information technology is moderate. Information technology is used to expand the market scope and seek information. Cultivation and market opportunities are the most information that young farmers need. The obstacles faced are internal group problems and insufficient time to integrate their business activities with information technology. Business assistance and information technology can help strengthen young farmer groups' management in agricultural entrepreneurship.